Features of Intellectual Property Rights Lending - Olga Fedorovna Maslenkova (Экономика региона, 2017)
The article describes the current situation in lending intellectual property (IP) rights in Russia. Furthermore, I investigate the existing legal framework for this type of lending. Special attention is paid to Russian and foreign literature review, including dissertations. The author studied the dynamics of lending trademarks license contracts and based on the official data of Federal Service for Intellectual Property of the Russian Federation archives and intellectual activity of 2009 — 2016. I describe borrowers and lenders as well as Russian regional banks having experience in intellectual property rights lending in 2014 — 2016. The author identified and commented the benefits of implementing such credit for a commercial bank and the company-borrower. Special attention is paid to difficulties and risks for both the lender and the borrower. The author has developed a mechanism of intellectual property rights lending, which describes procedures for parties. The study has defined the preferred algorithms for both the company-borrower and profitable bank. Moreover, I have described the “problem loan”, or late repayment of credit and interest. The paper describes conditions, which are necessary for the successful implementation of the developed credit schemes. I have revealed the impact of the Central Bank of the Russian Federation on the status of lending of IP and proposed measures to improve the situation. Recommendations of the author would help to promote secured bank lending of IP rights. This will have positive results for both the borrowers and the regional banks